Lupus manifestations in children with primary immunodeficiency diseases: Comprehensive phenotypic and genetic features and outcome. Issue 6 (2nd November 2021) - Al-Mayouf, Sulaiman M.; Alreefi, Hajar A.; Alsinan, Tuqa A.; AlSalmi, Ghada; AlRowais, Abdulaziz; Al-Herz, Waleed; Alazami, Anas M.; Alsonbul, Abdullah; Al-Mousa, Hamoud
Abstract: Objectives: To report the phenotypic, genetic findings and outcome of children with lupus manifestations associated with primary immunodeficiency diseases (PIDs). Methods: Data are retrospectively collected on patients with lupus manifestations and PIDs seen between 1998 and 2019. Data comprised the clinical findings and genetic testing, the response to treatment and the accrual damage related to SLE. Results: A total of 39 patients (22 female) were reviewed. Thirty-four patients had lupus manifestations and six patients with SLE-like manifestations. Genetic analysis was performed in 25 patients. Complement deficiency was the most frequent PIDs; 26 patients were C1q deficient, three patients had C3 deficiency, two patients had C4 deficiency and one patient with heterozygous C8b variant. The other seven patients had different PIDs genetic defects that include SCID caused by PNP deficiency, CGD, CVID ( PIK3CD), IL-2RB mutation, DNase II deficiency, STAT1 mutation, ISG15 mutation and Griscelli syndrome type 3. Mucocutaneous lesions, arthritis and lung involvement were the main clinical features. 84.1% experienced recurrent infections. The mean accrual damage was 2.7 ± 2.2. There were five deaths because of infection. Conclusion: This study suggests that patients with lupus manifestations and early onset disease, family history of SLE or recurrent infections should undergo immunological work-up and genetic testing to rule out PIDs.